Correlative study of FNAC and histopathology for breast lesions - Dr. Sreedevi CH; Dr. K Pushpalatha (Tropical Journal of Pathology and Microbiology)
Introduction: Fine needle aspiration cytology has become increasingly popular in diagnosis of palpable breast masses as it is sensitive, specific, expedient, economical and safe for screening of breast lesions. It has high sensitivity and specificity. The aim of the study was to categorize breast lesions and correlate the fine needle aspiration cytology diagnosis with histo-pathological findings. Methods: A Two years study was carried out on female and male patients with age 10-72, who visited hospital with complaint of breast lump, pain in the breast or discharge from the nipple. Results: Tumors on right breast is higher in percentage (54%) and 66% of tumors are less than 6 cm in size. Two cases, which found to be malignant with FNAC have become benign in biopsy test. Conclusion: The current study initiated to find the effectiveness of this technique and compared with biopsy methods.